Numerical simulation of natural convection in a concentric annulus between a square outer cylinder and a circular inner cylinder using the Taylor-series-expansion and least-squares-based lattice Boltzmann method - Peng, Y. (2014)
Physical Review E - Statistical, Nonlinear, and Soft Matter Physics